Meningkatkan Hasil Belajar Siswa dalam Mapel Matematika Melalui Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) pada Siswa Kelas VI SD Negeri Margoagung - Ika Saputri; Henry Aditia Rigianti (Warta Pendidikan | e-Journal, 2022)
This study aims to improve the learning outcomes of sixth graders at SD Negeri Margoagung on maple mathematics by using the Contextual Teaching Learning (CTL) learning model. The method used in this research is the description method. Furthermore, the data collection techniques used are interview and observation techniques. This research uses two cycles, each cycle consists of two meetings. The results of this study indicate that: (1) the skills of teachers in learning mathematics through the CTL learning model increase. (2) student activity in learning mathematics through the CTL learning model increases. (3) student learning outcomes in cycle I and cycle II have increased. The conclusion of this research is the application of the CTL learning model can improve the quality of student learning outcomes.